2016
DOI: 10.1186/s13643-016-0346-x
|View full text |Cite
|
Sign up to set email alerts
|

An evidence synthesis of the international knowledge base for new care models to inform and mobilise knowledge for multispecialty community providers (MCPs)

Abstract: BackgroundNHS England’s Five Year Forward View (NHS England, Five Year Forward View, 2014) formally introduced a strategy for new models of care driven by simultaneous pressures to contain costs, improve care and deliver services closer to home through integrated models. This synthesis focuses on a multispecialty community provider (MCP) model. This new model of care seeks to overcome the limitations in current models of care, often based around single condition-focused pathways, in contrast to patient-focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
11
0
3
Order By: Relevance
“…Further work has since been undertaken, 9,29,30 and more research is underway, which may help fill some of the gaps identified. [31][32][33] This review is complemented by a review of the wider academic and grey literature examining the development and impact of national and international initiatives with similarities to large-scale general practice organisations in England, such as specialist clinical networks, GP-led commissioning, out-of-hours cooperatives, and integrated care initiatives. 23 Comparison with existing literature Despite the recent focus by national policymakers in England on increasing organisational size to improve quality of care and generate efficiencies in general practice, there is no consistent association between scale, quality of care, or the generation of efficiency savings in the healthcare literature.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Further work has since been undertaken, 9,29,30 and more research is underway, which may help fill some of the gaps identified. [31][32][33] This review is complemented by a review of the wider academic and grey literature examining the development and impact of national and international initiatives with similarities to large-scale general practice organisations in England, such as specialist clinical networks, GP-led commissioning, out-of-hours cooperatives, and integrated care initiatives. 23 Comparison with existing literature Despite the recent focus by national policymakers in England on increasing organisational size to improve quality of care and generate efficiencies in general practice, there is no consistent association between scale, quality of care, or the generation of efficiency savings in the healthcare literature.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…from NHSE). 61 For all types of evidence, we focused on their theoretical or contextual contribution, recognising that formal quality assessment of such heterogeneous items would be of little value. For conceptual and contextual types of evidence, we employed a reflexive approach to locate the contribution of each item within the overall body of evidence and to assess its specific contribution.…”
Section: Review Methodologymentioning
confidence: 99%
“…57 The first eight candidates for ACSs were announced in June 2017, 59 with the remit to retain existing health INTRODUCTION NIHR Journals Library www.journalslibrary.nihr.ac.uk Chapter 2 Review methodology: stakeholder engagement, programme theory elicitation and analysis of the literature O n initiation, the review team registered a review protocol with the PROSPERO database and published an expanded version within a peer-reviewed journal. 61 This chapter first describes how we analysed existing logic models to identify programme theories and then engaged with stakeholders in order to verify and elucidate these potential programme theories. Subsequently, we conducted a systematic search of the relevant literature, supplemented by further purposive explorations for evidence, underpinning each programme theory component.…”
Section: Multispecialty Community Provider Progressmentioning
confidence: 99%
See 2 more Smart Citations